Oropharyngeal Stenosis Leading to an Unanticipated Difficult Airway in a Patient After Uvulopalatopharyngoplasty: A Case Report and Review of the Literature. Issue 5 (1st September 2018) - Boles, Kathryn S.; Casler, John D.; Porter, Steven B.
Abstract : Oropharyngeal stenosis can manifest as a rare complication after surgery for obstructive sleep apnea or tonsillectomy. Scar tissue formation from oropharyngeal stenosis may impede tracheal intubation or laryngeal mask airway insertion. We report the case of an asymptomatic adult woman found to have oropharyngeal stenosis after induction of anesthesia and discuss the management of this challenging scenario. We also contrast oropharyngeal stenosis with nasopharyngeal stenosis, another rare complication of uvulopalatopharyngoplasty. Abstract : Supplemental Digital Content is available in the text.